The Frog Xenopus as a Model to Study Joubert Syndrome: The Case of a Human Patient With Compound Heterozygous Variants in PIBF1 - Ott, Tim; Kaufmann, Lilian; Granzow, Martin; Hinderhofer, Katrin; Bartram, Claus R.; Theiß, Susanne; Seitz, Angelika; Paramasivam, Nagarajan; Schulz, Angela; Moog, Ute; Blum, Martin; Evers, Christina M. (Frontiers in Physiology, 2019)
Joubert syndrome (JS) is a congenital autosomal-recessive or - in rare cases - X-linked inherited disease. The diagnostic hallmark of the so-called molar tooth sign describes the morphological manifestation of the mid- and hindbrain in axial brain scans. Affected individuals show delayed development, intellectual disability, ataxia, hyperpnea, sleep apnea, abnormal eye and tongue movements as well as hypotonia. At the cellular level, JS is associated with the compromised biogenesis of sensory cilia, which identifies JS as a member of the large group of ciliopathies. Here we report on the identification of novel compound heterozygous variants (p.Y503C and p.Q485*) in the centrosomal gene PIBF1 in a patient with JS via trio whole exome sequencing. We have studied the underlying disease mechanism in the frog Xenopus, which offers fast assessment of cilia functions in a number of embryological contexts. Morpholino oligomer (MO) mediated knockdown of the orthologous Xenopus pibf1 gene resulted in defective mucociliary clearance in the larval epidermis, due to reduced cilia numbers and motility on multiciliated cells. To functionally assess patient alleles, mutations were analyzed in the larval skin: the p.Q485* nonsense mutation resulted in a disturbed localization of PIBF1 to the ciliary base. This mutant failed to rescue the ciliation phenotype following knockdown of endogenous pibf1. In contrast, the missense variant p.Y503C resulted in attenuated rescue capacity compared to the wild type allele. Based on these results, we conclude that in the case of this patient, JS is the result of a pathogenic combination of an amorphic and a hypomorphic PIBF1 allele. Our study underscores the versatility of the Xenopus model to study ciliopathies such as JS in a rapid and cost-effective manner, which should render this animal model attractive for future studies of human ciliopathies.